Isomerization/Recyclization of some 5-Ethoxycarbonyl-pyrimidines - Vardanyan, R S. (2005)
This communication reports on the investigation of a new recyclization conversion of a pyrimidine ring, which can be referred to as C-C recyclization. In this reaction the nucleophile cleaves the pyrimidine ring at the N(3)-C(4) bond, and following rotation around the single C(5)-C(6) bond the new cyclization takes place. This type of recyclization has general applicability, and takes place upon alkali treatment of substituted 4-methyl-5-ethoxycarbonyl- and 4-amino-5-ethoxycarbonyl-pyrimidines (1) which are transformed respectively to 4-hydroxy-5-acetyl- and 4-hydroxy-5-carbamoylpyrimidines (2). The obtained pyrimidyl-ketones can be readily converted to their hydrazones 7–12.